2017
DOI: 10.1016/j.psyneuen.2017.07.410
|View full text |Cite
|
Sign up to set email alerts
|

Gonads and strife: Sex hormones vary according to sexual orientation for women and stress indices for both sexes

Abstract: a b s t r a c tThis study assessed sexual orientation and psychobiological stress indices in relation to salivary sex hormones as part of a well-validated laboratory-based stress paradigm. Participants included 87 healthy adults that were on average 25 years old who self-identified as lesbian/bisexual women (n = 20), heterosexual women (n = 21), gay/bisexual men (n = 26), and heterosexual men (n = 20). Two saliva samples were collected fifteen minutes before and fifteen minutes after exposure to a modified Tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
(107 reference statements)
1
3
0
Order By: Relevance
“…In analyses that adjusted for key covariates, we found that lesbian/bisexual women had higher overall testosterone and progesterone concentrations as a group than heterosexual women, while men showed no differences in HPG axis functioning by sexual orientation. 160 That lesbian/bisexual women would manifest higher overall levels of testosterone is in accord with some existing reports, 163,164 but also in disaccord with studies showing no differences. 165,166 As discussed earlier, a longstanding proposal of this mixed literature has been that elevated androgens among sexual minority women might be explained by environmental stress.…”
Section: Sexual Orientation and Gc Functioningsupporting
confidence: 78%
See 2 more Smart Citations
“…In analyses that adjusted for key covariates, we found that lesbian/bisexual women had higher overall testosterone and progesterone concentrations as a group than heterosexual women, while men showed no differences in HPG axis functioning by sexual orientation. 160 That lesbian/bisexual women would manifest higher overall levels of testosterone is in accord with some existing reports, 163,164 but also in disaccord with studies showing no differences. 165,166 As discussed earlier, a longstanding proposal of this mixed literature has been that elevated androgens among sexual minority women might be explained by environmental stress.…”
Section: Sexual Orientation and Gc Functioningsupporting
confidence: 78%
“…To further triangulate methods and facilitate interpretation of these complex associations, we ran an analysis assessing intercorrelations among the HPG axis and HPA axis dynamics. 160 We found that cortisol dynamics (area under the curve formulas) were positively associated with testosterone and progesterone fluctuations while accounting for age, sex, gender roles, and sexual orientation. This supplemental result underlines the need to account for HPG axis functioning in studies of GC dynamics.…”
Section: Sexual Orientation and Gc Functioningmentioning
confidence: 74%
See 1 more Smart Citation
“…There was an association between allostatic load and genderrelated characteristics (e.g., androgynous and un differentiated individuals, masculinity levels), as well as sexual orientation (i.e., lesbian, gay, and bisexual indi viduals) [118][119][120][121][122].…”
Section: General Population Studies Sociodemographic Correlatesmentioning
confidence: 99%